Sex differences in neural correlates of common psychopathological symptoms in early adolescence. Issue 14 (26th October 2022) - Biondo, Francesca; Thunell, Charlotte Nymberg; Xu, Bing; Chu, Congying; Jia, Tianye; Ing, Alex; Quinlan, Erin Burke; Tay, Nicole; Banaschewski, Tobias; Bokde, Arun L. W.; Büchel, Christian; Desrivières, Sylvane; et al.
Abstract: Background: Sex-related differences in psychopathology are known phenomena, with externalizing and internalizing symptoms typically more common in boys and girls, respectively. However, the neural correlates of these sex-by-psychopathology interactions are underinvestigated, particularly in adolescence. Methods: Participants were 14 years of age and part of the IMAGEN study, a large ( N = 1526) community-based sample. To test for sex-by-psychopathology interactions in structural grey matter volume (GMV), we used whole-brain, voxel-wise neuroimaging analyses based on robust non-parametric methods. Psychopathological symptom data were derived from the Strengths and Difficulties Questionnaire (SDQ). Results: We found a sex-by-hyperactivity/inattention interaction in four brain clusters: right temporoparietal-opercular region ( p < 0.01, Cohen's d = −0.24), bilateral anterior and mid-cingulum ( p < 0.05, Cohen's d = −0.18), right cerebellum and fusiform ( p < 0.05, Cohen's d = −0.20) and left frontal superior and middle gyri ( p < 0.05, Cohen's d = −0.26). Higher symptoms of hyperactivity/inattention were associated with lower GMV in all four brain clusters in boys, and with higher GMV in the temporoparietal-opercular and cerebellar-fusiform clusters in girls. Conclusions: Using a large, sex-balanced and community-based sample, our study lends support to the idea that externalizing symptoms of hyperactivity/inattention may be associated with different neural structures in male and female adolescents. The brain regions we report have been associated with a myriad of important cognitive functions, in particular, attention, cognitive and motor control, and timing, that are potentially relevant to understand the behavioural manifestations of hyperactive and inattentive symptoms. This study highlights the importance of considering sex in our efforts to uncover mechanisms underlying psychopathology during adolescence.